Values in higher education teaching - Harland, Tony, 1955-; Pickering, Neil. (Abingdon, oxon : Routledge, 2011)
'Values in Higher Education Teaching' explores the way in which teaching, research, learning and higher education are a values enterprise and that an exploration of values is necessary to work out the full purposes of a higher education to guide practices and help academics understand academic work.
Includes bibliographical references (p. [121]-123) and index.
Keywords: College teachers -- Training of -- Case studies; Universities and colleges -- Faculty -- Case studies; Education, Higher -- Case studies; Curriculum enrichment -- Case studies